A quantitative study of teacher trainees’ experiences of board game pedagogy - Kocsis, Zsófia; Szilágyi, Beatrix; Ecsedi, Zoárd (Central European Journal of Educational Research, 2025)
Nowadays, educating the young generation is a challenge for educators, as traditional teaching methods are no longer sufficient (Khalaf & Zin, 2018), so teaching methods that build not only on the cognitive but also on the social and emotional dimensions of learning must be used (Illeris, 2010; Lim et al, 2019.) Board game pedagogy is proving to be a useful method for solving the problems of 21st century education: board games can be used to introduce new topics or to teach specific parts of the curriculum (Damsa & Fromann, 2016; Antonaci et al, 2015). In our quantitative, pilot study (n=103), we seek to answer the question of the extent to which teacher trainees are familiarised with board game pedagogy during their training, and to assess the frequency of didactic methods and working methods used by university teachers. Of the students surveyed, only 54 had heard of board game pedagogy, a large proportion of them consider it to be a motivating and effective teaching tool and would like it to be part of their training. Regarding the variety of working methods and forms of work of university teachers, the more traditional methods of lecture and explanation, as well as individual and frontal forms of work, predominate. Despite these limitations, we have data that could serve as a basis for future research and could also contribute to the development of teacher education.